ОКСЮМОРОН – НУТҚДА ҒАЙРИОДАТИЙ БИРИКМАЛАР ҲОСИЛ ҚИЛИШ УСУЛЛАРИДАН БИРИ (Scientific journal of the Fergana State University, 2023)
This article talks about an oxymoron – one of the form of a methodological tool that relies on logical and emotional relationships that help to increase impressionability through lexico-semantic and linguistic-stylistic events.